The short-term effect of smartphone usage on the upper-back postures of university students. Issue 1 (1st January 2019) - Cochrane, Maria Elizabeth; Tshabalala, Muziwakhe Daniel; Hlatswayo, Nkateko Climax; Modipana, Rosina Mahlatse; Makibelo, Pertunia Phuti; Mashale, Exaggerate Potego; Pete, Lerato Caroline
Abstract: The purpose of the current study was to determine the short-term effects of smartphone usage on the upper-back postures of university students. Sixty-three students completed a self-administered questionnaire and photographic postural analysis. Smartphone usage significantly affected shoulder protraction on the non-dominant side (p = 0.000); thoracic kyphosis (p = 0.000); lateral neck flexion (p = 0.029 left and p = 0.001 right) and pelvic obliquity (p = 0.000 left and right). The results indicate that smartphones negatively affect the postures of university students and may result in severe long-term clinical implications such as chronic neck-, thoracic- and low back pain, headaches and decreased concentration.